Association of demographics, cardiovascular indicators and disability characteristics with 7-year coronary heart disease incident in persons with disabilities - Husheng Li; Yiyan Wang; Yan Xue; Yao Li; Hengjing Wu; Jing Wu (BMC, 2023)
Abstract Objective Previous studies had demonstrated that disability increases mortality in patients with coronary heart disease (CHD). However, for people who had been disabled but do not have baseline cardiovascular disease, there is still limited data on how they might develop CHD. This study aimed to investigate the incidence and predictors of CHD in people with disabilities. Methods We conducted a 7-year retrospective study utilizing data from the Shanghai Comprehensive Information Platform for Persons with Disabilities Rehabilitation. Subjects aged over 18 years with at least four annual complete electronic health records were included. The primary outcome was CHD, defined as ischemic heart disease or myocardial infarction. Kaplan-Meier analysis and log-rank tests were used to compare cumulative CHD for sub-populations, stratified by age, gender, and the classification of disabilities. Cox regression was used to identify the potentially important factors. Results Out of 6419 persons with disabilities, 688 CHD cases (mean age 52.95 ± 7.17 years, male 52.2%) were identified, with a cumulative incidence of 10.72% and an incidence density of 15.15/1000 person-years. The incidence density of CHD is higher in the male gender, people over 45 years, and those with physical disabilities. Male (HR = 1.294, 95% CI, 1.111-1.506), hypertension (HR = 1.683, 95% CI, 1.405-2.009), diabetes mellitus (HR = 1.488, 95% CI, 1.140-1.934), total cholesterol (HR = 1.110, 95% CI, 1.023-1.204), and physical disabilities (HR = 1.122, 95% CI, 1.019-1.414) were independently associated with CHD. Conclusion The findings indicate that the incidence of CHD differs across disability categories rather than the severity of disability. People with physical disabilities had significantly higher risks for the development of CHD. The underlying physiological and pathological factors need to be further studied.